2010
DOI: 10.1152/ajpregu.00099.2010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aging on cardiac function during cold stress in humans

Abstract: determine whether skin surface cooling increases left ventricular preload and contractility to a greater extent in older compared with young adults we studied 11 young (28 Ϯ 2 yr; means Ϯ SE) and 11 older (64 Ϯ 3 yr) adults during normothermia (35°C water perfused through a tube-lined suit) and cooling (15°C water perfused for 20 min) using standard and tissue Doppler echocardiography. Cooling significantly decreased skin surface temperature in young (⌬2.8 Ϯ 0.3°C) and older (⌬3.0 Ϯ 0.3°C) adults and increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
42
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 40 publications
5
42
0
3
Order By: Relevance
“…Whole body cold stress elicits a robust systemic pressor response (3,4,9,23,62) that is exaggerated in aged adults, evidenced by this and other (23,60) studies. The augmented pressor response to skin surface cooling in older adults is likely not mediated by an increase in cardiac output, as cardiac output derived via transthoracic echocardiography remains unchanged throughout cooling in older adults (60).…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…Whole body cold stress elicits a robust systemic pressor response (3,4,9,23,62) that is exaggerated in aged adults, evidenced by this and other (23,60) studies. The augmented pressor response to skin surface cooling in older adults is likely not mediated by an increase in cardiac output, as cardiac output derived via transthoracic echocardiography remains unchanged throughout cooling in older adults (60).…”
Section: Discussionsupporting
confidence: 70%
“…The augmented pressor response to skin surface cooling in older adults is likely not mediated by an increase in cardiac output, as cardiac output derived via transthoracic echocardiography remains unchanged throughout cooling in older adults (60). The results of the present study indicate that pronounced increases in MSNA during cold stress in older adults may contribute to the greater pressor response.…”
Section: Discussionmentioning
confidence: 43%
See 2 more Smart Citations
“…Cardiac death is highest in the winter months, even in people who spend little time outdoors (45,54). While the effects of lowered skin temperature on cardiovascular function have been extensively studied (10,29,59,60), other mechanisms likely play a role in this process.Physical perturbation of the oropharynx and larynx elevates blood pressure in clinical settings (18,34), and laryngeal cold receptors have been identified in animals (38, 51). Previous studies (26,28,35,37) have shown that blood pressure, heart rate, and/or muscle sympathetic nerve activity are increased with cold air breathing in healthy humans.…”
mentioning
confidence: 99%